Engineering Thermoanaerobacterium aotearoense SCUT27 with argR knockout for enhanced ethanol production from lignocellulosic hydrolysates. (August 2020) - Qu, Chunyun; Chen, Lili; Fu, Hongxin; Wang, Jufang
Highlights: Among these three ArgRs, ArgR1864 greatly affected substrate utilization in SCUT27. Deletion of argR 1864 notably improved xylose utilization, due to higher energy level. A new carbon flux prone to ethanol synthesis had been established in SCUT27/Δ argR1864 . SCUT27/Δ argR1864 showed better performances on ethanol production with hydrolysates. Abstract: Although Thermoanaerobacterium aotearoense SCUT27 (SCUT27) could co-utilize glucose and xylose, the presence of glucose still repressed xylose catabolism. Arginine repressors (ArgRs) were involved in several key metabolic pathways and might be the global regulator. In SCUT27, three genes (V518_0585; V518_1870; V518_1864) were annotated as argR and only the deficiency of argR1864 could greatly improve the co-utilization of glucose and xylose, due to the enhanced activity of xylose isomerase, xylulokinase and the higher energy level. The metabolic flux of SCUT27/Δ argR1864 indicated that new carbon distribution had been re-established and the ethanol yield had increased by 82.95%, strains growth and acetate yield improved by 35.91% without detectable lactate for the poor activity of lactate dehydrogenase. The improved concentration of ATP and NAD(H) in SCUT27/Δ argR1864 provided more energy to respond the stress, which enabled the mutant the better cell viability to utilize lignocellulosic hydrolysates for enhanced ethanol formation.